Implementation of Learning Implementation of the Scouting Level Extracurricular Program in Junior High School 10 Padang - Ranni Andra; Tasril Bartin (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is motivated by the high interest of students in scouting extracurricular activities at SMP 10 Padang. It is suspected that one of the factors is caused by the good implementation of scout extracurricular activities conducted by the coach. This study aims to provide information on: 1) learning planning, 2) implementation of learning, 3) evaluation of learning for scouting extracurricular programs at level 10 at SMPN Padang. This research uses quantitative approach, type of descriptive research. The study population consisted of 60 students taking part in the Boy Scout extracurricular activities. Samples taken in this study were 50%. The number of samples is 30 people. The sampling technique uses stratified random sampling. Data collection techniques using a questionnaire, with data collection tools in the form of a list of statements. Data analysis techniques using the percentage formula. From the results of the study it was found that (1) Scout extracurricular program learning planning is very good, (2) Scout extracurricular program learning is very good, (3) evaluation of scout extracurricular learning programs is very good. The conclusion of this research is that learning scout extracurricular programs in SMP Negeri 10 Padang is very good. Suggestions to the organizers of the Boy Scout extracurricular program can maintain and improve the implementation of the program to be even better.Keywords: Implementation of Learning, Scout Extracurricular Activities